2017
DOI: 10.1186/s12974-017-0851-4
|View full text |Cite
|
Sign up to set email alerts
|

In vivo TSPO and cannabinoid receptor type 2 availability early in post-stroke neuroinflammation in rats: a positron emission tomography study

Abstract: BackgroundUpregulated levels of 18-kDa translocator proteins (TSPO) and type 2 endocannabinoid receptors (CB2) are considered to reflect different aspects of microglia-related neuroinflammatory responses in the brain. Relative to the increase in the TSPO expression that occurs slightly later during neuroinflammation in a proinflammatory fashion, CB2 activation is considered to relate to the neuroprotective responses that occurs predominantly at an early stage of brain disorders. These findings, however, were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…Interestingly, our direct comparison between [ 18 F]FDG SUVR and [ 11 C]DPA713 BP ND showed a positive correlation in the right hippocampus and amygdala. Since it was reported that TSPO-based PET findings in chronic, but not early, brain disease reflect a proinflammatory state [35,36], it seems theoretically possible that lower cerebral metabolism couples with higher proinflammatory responses, i.e., [ 18 [37], from aerobic glycolysis, the current result suggested that the higher [ 18 F]FDG uptake accompanied greater glycolysis in the hippocampus and amygdala, which subserve memory and emotion in patients with FSS. In the present study, a significant reduction in glucose metabolism was found in patients with FSS compared with healthy subjects.…”
Section: Discussionmentioning
confidence: 51%
“…Interestingly, our direct comparison between [ 18 F]FDG SUVR and [ 11 C]DPA713 BP ND showed a positive correlation in the right hippocampus and amygdala. Since it was reported that TSPO-based PET findings in chronic, but not early, brain disease reflect a proinflammatory state [35,36], it seems theoretically possible that lower cerebral metabolism couples with higher proinflammatory responses, i.e., [ 18 [37], from aerobic glycolysis, the current result suggested that the higher [ 18 F]FDG uptake accompanied greater glycolysis in the hippocampus and amygdala, which subserve memory and emotion in patients with FSS. In the present study, a significant reduction in glucose metabolism was found in patients with FSS compared with healthy subjects.…”
Section: Discussionmentioning
confidence: 51%
“…(5) Imaging results using CB 2 R and TSPO tracers should be compared head to head. Given that CB 2 R more closely represents anti-inflammatory features, additional knowledge of the inflammatory status in the CNS will be provided by PET imaging using both CB 2 R and TSPO tracers [43]. 6The mRNA expression of CB 2 R should be measured.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they might not be the most suitable for evaluating of CB 2 R. CB 2 R imaging in an animal model of stroke Ischemic stroke involves a cascade of hemodynamic, vascular, structural, and inflammatory responses in a time-dependent manner [54][55][56]. Inflammation is implicated in the initial neuronal loss and consists mainly of pro-inflammatory responses and the extension of the lesion in the penumbra; the subsequent [43] was reported in an SD rat model of photothrombotic stroke at 24 h after surgery. Another study using [ 11 C]NE40 imaging did not show an upregulated signal in a Wistar rat model of photothrombotic stroke [48], despite the minor increase in the level of CB 2 R seen by immunostaining.…”
Section: Cb 2 Imaging In Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Positron emission tomography (PET) based on operation of biologically active compounds labeled with short‐lived isotopes 11 C (T 1/2 =20.4 min) and 18 F (T 1/2 =109.8 min) provides a non‐invasive and direct method for assessing neuroinflammatory changes in the brain . Recently, significant progress was achieved in the development of PET radiotracers for inflammatory protein targets, including enzymes (translocator protein 18 kDa, glycogen synthase kinase 3, monoamine oxidase‐B, cyclooxygenase), cannabinoid (CB2) and purine (P2X7) receptors . Cyclooxygenase type 2 (COX‐2) is an inducible enzyme involved in the prostaglandin biosynthesis, it is minimally expressed at baseline in several peripheral tissues and brain, and overexpressed at sites of inflammation.…”
Section: Figurementioning
confidence: 99%